PHYTOPHARMACOLOGICAL PROFILE AND BRINE SHRIMP LETHALITY ASSAY OF THE METHANOLIC AND ETHANOLIC EXTRACTS OF THE LEAF AND BARK OF SYMPLOCOS COCHINCHINENSIS. - R.KALPANA; Dr. R. DHAMOTHARAN (International Journal of Pharma and Bio Sciences, 2016)
Cancer is one of the deadliest diseases in the world. Researchers all over the world are in constant search for new drugs to cure cancer. Traditional medicinal practices have utilized various plant sources for the treatment of cancer. Medical scientists all over the world have started exploring the traditional medicinal practices to prepare new formulations to treat cancer. The present study is one such approach. The cytotoxicity of the methanolic and ethanolic extracts of the leaf and bark powder of Symplocos cochinchinensis against brine shrimp larvae is done for the first time. It was found that the ethanolic extracts of the leaf showed 100% mortality at 2 mg/ml concentration in the 24th hour. The methanolic and ethanolic extracts of the bark showed 100% mortality at 3 mg/ml concentration in the 24th hour. The methanolic and ethanolic extracts of Symplocos cochinchinensis showed the presence of various phytoconstituents like phenols, flavonoids, tannins, saponins and glycosides. The methanolic extract of the leaf has the maximum phytoconstituents viz. Total phenolic content of 13.67+0.29mgTAE/g dry weight of the plant material., Total flavonoid content 6.34+0.4 μgQE/g dry weight of the plant material.. The free radical scavenging activity of the extracts was done by Ferric Thiocyanate (FTC), Ferric reducing antioxidant power (FRAP), Thiobarbituric acid (TBA) and [2,2_ -Azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)] (ABTS) assays. The methanolic extract of the leaf showed the maximum inhibition in the FTC method (84.54%) and TBA (88.89%) assays. Methanolic extract of the bark has the maximum ability to reduce ferric ions (73.74%) as revealed by the FRAP assay. The ethanolic extract of the leaf was found to scavenge the ABTS radicals to a higher extent (55.71% in ABTS assay). In the present study the methanol and ethanol extracts of the leaf and bark of S.cochinchinensis was found to have free radical scavenging activity as shown by the 2, 2 – Diphenyl-1- picryl hydrazyl (DPPH) assay.The phytopharmacological profile of the two extracts of the leaf and bark of S.cochinchinensis are also analysed. This study proves that the methanolic and ethanolic extracts of the leaf and bark of S.cochinchinensis are potential candidates for further research.